An Analysis of Code-Mixing Usage in WhatsApp Groups Conversation among Lecturers of Universitas Pamulang - Haryati Haryati; Ratu Prayuana (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
This study was aimed to find out the kinds of code-mixing used by lecturers from some departments and the factors of using code mixing. This study was a descriptive qualitative analysis that attempted to describe the kinds of code-mixing and the factors. The participants of this study were lecturers from 4 different groups of Universitas Pamulang. The participants were selected based on the purposive sampling in order to support the research finding. The data were taken from questionnaire and observation on WhatsApp groups to seek the factors and to classify the types of code-mixing. As the results, the writers found the group of Pelatih TOEFL produced 15 congruent lexicalization, 4 insertion and 0 alternation. The group of Penelitian Internal Unpam produced 15 congruent lexicalization, 6 insertion and 2 alternation. The group of Sastra Unpam produced 9 congruent lexicalization, 10 insertion and 5 alternation. The group of Prodi Sasing produced 17 congruent lexicalization, 3 insertion and 5 alternation. In addition, the distribution of questionnaire resulted the factors of applying code-mixing on all WhatsApp groups. Bilingualism (38%), speaker and interlocutor (4%), situation (5%), vocabulary (46%) and prestige (8%) are the factors found in Pelatih dan Pengawas TOEFL group. Bilingualism (21%), speaker and interlocutor (11.11%), situation (22%), vocabulary (38%) and prestige (8%) are the factors found in Peenelitian Internal Unpam group. Bilingualism (48%), speaker and interlocutor (5%), situation (13%), vocabulary (34%) and prestige (0%) are the factors found in Sastra Unpam group. Bilingualism (55%), speaker and interlocutor (5%), situation (7%), vocabulary 67%) and prestige (12%) are the factors found in Sastra Unpam group.